Roots to Grow and Wings to Fly: An Ethnography of Psychosocial Development in Adolescent Performance Sport - Sergio Lara-Bercial; Jim McKenna (MDPI AG, 2022)
This study aimed to explore the potential for sport to support psychosocial development in young people in a youth performance setting using a novel realistic evaluation approach. Part 1 of this two-paper series published in this Special Issue identified the programme theories-how the programme is supposed to work. A wide and deep network of context, generative mechanisms and outcomes responsible for psychosocial development in this youth performance basketball club emerged. The first paper also concluded that the outcomes and the experience are highly contextual and individualised. In this second part, the stakeholder's programme theories were tested during a full-season ethnography of the same club. Immersion in the day-to-day environment generated a fine-grain analysis of the processes involved, including: (i) sustained attentional focus; (ii) structured and unstructured skill-building activities; (iii) deliberate and incidental support; and (iv) feelings indicating personal growth. Personal development in and through sport is thus shown to be conditional, multi-faceted, time-sensitive and idiosyncratic. The findings of this two-part study are considered to propose a model of psychosocial development in and through sport. This heuristic tool is presented to support sport psychologists, coaches, club administrators and parents to deliberately create and optimise developmental environments.